Effects of Na content in Na/Ni/SiO2 and Na/Ni/CeO2 catalysts for CO and CO2 methanation - Le, Thien An; Kim, Tae Wook; Lee, Sae Ha; Park, Eun Duck (Catalysis Today, 2018)
CO and CO2 methanation over Na/Ni/SiO2 and Na/Ni/CeO2 catalysts with different Na contents (0, 0.1, and 1 wt%) were studied. N2 physisorption, H2 chemisorption, temperature-programmed reduction with H2, CO2 chemisorption, temperature-programmed desorption of CO2, temperature-programmed oxidation, X-ray diffraction, X-ray photoelectron spectroscopy, and transmission electron microscopy were employed to characterize the catalysts. Even just 0.1 wt% Na was observed to have a negative effect on CO methanation for the Na/Ni/SiO2 and Na/Ni/CeO2 catalysts owing to surface blockage of the Ni metal. The negative effect of Na on CO2 methanation was also observed for the Na/Ni/CeO2 catalysts. Conversely, Na exhibited a positive effect upon CO2 methanation over the Na/Ni/SiO2 catalysts. The different effect of Na on CO2 methanation is closely related to the amount of CO2 chemisorbed on the catalysts. Stable catalytic activity for CO and CO2 methanation was observed for Ni/SiO2, Na/Ni/SiO2, and Ni/CeO2. However, the Na/Ni/CeO2 catalyst was deactivated during CO methanation owing to coke formation following olefin production. However, this catalyst was stable for CO2 methanation.
Keywords: Co methanation; Different effects; N2 physisorption; Ni/CeO2; Ni/SiO2; Olefin production; Temperature programmed oxidation; Temperature-programmed reduction; CO methanation; CO2 methanation; Ni/CeO2; Ni/SiO2; Sodium